Review on the application status of antibiotic water pollution and treatment technology in China - Li Yanan; You Sifan; Yan Ruyan; Song Yang (E3S Web of Conferences)
Antibiotics are drugs that can kill or inhibit the growth of microorganisms, and are widely used in medical and health care, animal husbandry, agricultural planting and other industries. In recent years, the output of active pharmaceutical ingredients in China has shown a significant growth trend, and the per capita use of antibiotics has reached ten times as high as that in the United States [1]. From 2010 to 2020, the discharge of antibiotics from 80 common veterinary drugs was as high as 23,110 tons ~ 40,850 tons/year. According to the data of the World Health Organization, the utilization rate of antibacterial drugs among inpatients in the world is about 30%. With the wide use of antibiotics in the world, its residue and influence in the water environment have been paid more and more attention. The unreasonable use of human beings leads to the increasing concentration of antibiotics in the environment, which seriously threatens human health and destroys the stability of the ecological environment system. This paper summarizes and analyzes the current situation of antibiotic water pollution in China, and also evaluates the advantages and limitations of different treatment methods in order to provide reference for scientific research.